2012
DOI: 10.1208/s12248-012-9422-x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Beads-Based Dissolution Method for the In Vitro Evaluation of Extended Release HPMC Matrix Tablets and the Correlation with the In Vivo Data

Abstract: Abstract. The aim of this work was to establish alternative in vitro dissolution method with good discrimination and in vivo predictability for the evaluation of HPMC extended release matrix tablets. For this purpose, two different HPMC matrix tablet formulations were first evaluated by a range of conventional dissolution testing methods using apparatus 1, apparatus 2, and apparatus 3 according to US Pharmacopoeia. Obtained results showed low discrimination between the tested samples. Afterward, a novel dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 43 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…the Levy plot (Levy et al, 1965), is nonlinear. While in most cases a linear time transformation proved sufficient (Brockmeier et al, 1985;Schliecker et al, 2004;Nishimura et al, 2007;Jantratid et al, 2009;Cardot and Davit, 2012), several reports have found that / is a convex function, i.e., the Levy plot shows an upward curvature (Drewe and Guitard, 1993;Humbert et al, 1994;Hemmingsen et al, 2011;Cardot and Davit, 2012;Kakhi et al, 2013;Klancar et al, 2013). It will be shown in this study that this means that dissolution is decelerated in vivo (a < 1), or respectively, accelerated in vitro, and that the Levy plot can be described by a power function.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…the Levy plot (Levy et al, 1965), is nonlinear. While in most cases a linear time transformation proved sufficient (Brockmeier et al, 1985;Schliecker et al, 2004;Nishimura et al, 2007;Jantratid et al, 2009;Cardot and Davit, 2012), several reports have found that / is a convex function, i.e., the Levy plot shows an upward curvature (Drewe and Guitard, 1993;Humbert et al, 1994;Hemmingsen et al, 2011;Cardot and Davit, 2012;Kakhi et al, 2013;Klancar et al, 2013). It will be shown in this study that this means that dissolution is decelerated in vivo (a < 1), or respectively, accelerated in vitro, and that the Levy plot can be described by a power function.…”
Section: Introductionmentioning
confidence: 63%
“…(14)) may be applicable. Interestingly,Klancar et al (2013) already fitted a t in vivo -t in vitro -plot by a Release profiles and fractional release rate functions simulated for accelerated (a = 2) and decelerated (a = 0.5) drug release using Eqs. Baseline release profile (37°) fitted by an IG distribution (Eq.…”
mentioning
confidence: 99%
“…Test DT4 was done with a USP 3 apparatus containing plastic beads to exert high mechanical stress on the tablets. This test was developed in our group and is only briefly presented here (22). A total of 250 mL of dissolution media was poured into each dissolution vessel and placed in a water bath to maintain a temperature of 37±0.5°C.…”
Section: Dissolution Testingmentioning
confidence: 99%
“…A USP 3 apparatus in combination with plastic beads was also used to apply additional mechanical stress to HPMC matrices with a model drug with low solubility (22). It was shown that applying the stress using the beads was crucial in discriminating the tablets in vitro and in establishing a good correlation with in vivo data.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different parameters affecting in vitro drug release, the hydrodynamic condition (agitation intensity) and mechanical destructive forces play a significant role in drug release from hydrophilic matrices (25,26). However, the in vivo drug release can differ from the predicted in vitro, due to extensive mechanical forces in the GI tract (26)(27)(28)(29). Therefore, the design of a mechanically robust formulation (which can be defined by sufficient gel strength) is a key to achieve predictable in vivo plasma concentrations (6).…”
Section: Introductionmentioning
confidence: 99%